A world of homeowners : American power and the politics of housing aid - Kwak, Nancy, 1973- (Chicago : The University of Chicago Press, 2015)
Is there anything more American than the ideal of homeownership? In this groundbreaking work of transnational history, Nancy H. Kwak reveals how the concept of homeownership became one of America's major exports and defining characteristics around the world.
Building a new American model of homeownership -- Combatting communism with homeownership -- Homeownership in an era of decolonization -- Homeownership as investment -- Fair homeownership -- A homeownership consensus? -- Conclusion.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Home ownership -- United States -- History -- 20th century; Home ownership -- Political aspects -- United States; Housing policy -- United States; Federal aid to housing -- United States -- History -- 20th century; Federal aid to housing -- Political aspects -- United States; Logement -- Politique gouvernementale -- États-Unis.; Aide de l'État au logement -- États-Unis -- Histoire -- 20e siècle.; Aide de l'État au logement -- Aspect politique -- États-Unis.; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Federal aid to housing; Home ownership; Home ownership -- Political aspects; Housing policy; United States; Wohneigentum; Wohnungspolitik; USA; 1900-1999; History